Metode Analytical Hierarchy Process Dalam Menentukan Pemilihan Desa Terbaik - Tri Rahayu; Erly Krisnanik; Bayu Hananto (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
The purpose of this study is to make decisions using the Analytical Hierarchy Prosess (AHP) method in determining the best village. Criteria for determining the best village; namely Community Economy, Public Health, Education, Security and Order and Community Institutions. The results of the calculations using the AHP method in the paired criteria comparison matrix, calculate the eigenvalue until the consistency test. The results of the calculation criteria obtained are: Public Health (45%), Community Economy (24%), Education (16%), Security and Order (9%) and Community Institutions (6%). So that the highest criteria obtained are public health and the lowest, namely community institutions